Analisa Kinerja Pengelolaan Irigasi Di Daerah Irigasi Lemor, Kabupaten Lombok Timur, Nusa Tenggara Barat: Performance Analysis On Irrigation Management At Lemor Irrigation Area, East Lombok, West Nusa Tenggara - Jannata Jannata; Sirajuddin Haji Abdullah; Asih Priyati (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2015)
The purpose of this study were to analyze technical aspect on irrigation asset inventory, sufficient levels of irrigation water, farmers’ satisfaction level on manager irrigation performance and the irrigation management. This research was conducted directly in the field by collecting data that further analyzed using qualitative data tables (descriptive) by simple statistical analysis. The analysis results showed that: (1) Based on technical aspect, the irrigation asset inventory at Lemor area was categorized at ‘properly well condition’ as the damage only had been found in the form of seepage; (2) The available irrigation water was not sufficient to supply the rice field on Lemor area, showed by average water discharge per two-weeks in 2012, 2013, and 2014 respectively were 72-105.575 litre/second, 72-99.485 litre/second, 72-105.115 litre/second whereas required water for irrigation were 156.09-344.097 liter/second, 133-344.097 liter/second, 110.418-338.025 litre/second respectively; (3) Total difference on correction factor in 2012 showed 0.003-0.568, which means rotation was necessary despite the sixth of two-weeks, MT II and the seventh and eight of two-weeks showed value of correlation factor higher than 0.75. As well as in 2013 and 2014, from soil preparation until growth phase of the sixth of two-weeks, the correlation factor were less than 0.75, yet at growth phase the seventh and eight of two weeks the correlation factor were above 0.75; (4) Simultaneous planting and monoculture planting were not able to meet the required irrigation water; (5) Farmers satisfaction level on the irrigation network management by service indicator, water demand condition, maintenance of irrigation channels, and the discharge channel (drainage) were 97.25, 96.25, 92.60, and 70.25 respectively. The average result showed that the irrigation management was effective; (6) The effectiveness of irrigation management in Lemor area was due to high participation of farmers either in financial process or in channel maintenance phase.Keywords: Irrigation, Asset Inventory, Irrigation Management